2022
DOI: 10.1002/anie.202208640
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Chelatable Porphyrinic Frameworks for Single‐Cell Multiplexing with Mass Cytometry

Abstract: Single‐cell multiplexing is key to exploration of the heterogeneous cell populations in biological systems. Although the state‐of‐the‐art mass cytometry (CyTOF) possesses high resolution and multiple dimensions, the lack of suitable marker materials prohibits fully exploiting the available CyTOF detection channels. Here we report a new design strategy for CyTOF markers using functionalized mesoporous porphyrinic frameworks (MPFs) as scaffolds for chelating metals that have been unachievable by conventional app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Four absorption peaks are clearly observed in the Q-band (450–700 nm) of metal-free TCPP, while CuTCPP­(Cu) has only one absorption peak in the Q-band, and the red-shift occurs at the same time, demonstrating the formation of metalloporphyrin (Figure S4). , The comparison of FT-IR spectra of metal-free porphyrin and metalloporphyrin is shown in Figure S5. The stretching vibration peak of N–H on the pyrrole ring at 3320 cm –1 disappears, and the absorption peak at 964 cm –1 is caused by the out-of-plane deformation of C–N red-shift to 1001 cm –1 due to the stretching vibration of the Cu–N coordination bond, which provides strong evidence for the successful formation of CuTCPP­(Cu) .…”
mentioning
confidence: 99%
“…Four absorption peaks are clearly observed in the Q-band (450–700 nm) of metal-free TCPP, while CuTCPP­(Cu) has only one absorption peak in the Q-band, and the red-shift occurs at the same time, demonstrating the formation of metalloporphyrin (Figure S4). , The comparison of FT-IR spectra of metal-free porphyrin and metalloporphyrin is shown in Figure S5. The stretching vibration peak of N–H on the pyrrole ring at 3320 cm –1 disappears, and the absorption peak at 964 cm –1 is caused by the out-of-plane deformation of C–N red-shift to 1001 cm –1 due to the stretching vibration of the Cu–N coordination bond, which provides strong evidence for the successful formation of CuTCPP­(Cu) .…”
mentioning
confidence: 99%
“…Very recently, Chen et al reported a porphyrin-based nMOF for SMC analyses. Their system was based on PEG-functionalized PCN-224, where PCN refers to a porous coordination network consisting of Zr-oxo clusters and 5,10,15,20-tetrakis (4-carboxyphenyl) porphyrin ligands.…”
Section: Nanoparticle (Np) Mass Tag Reagentsmentioning
confidence: 99%
“…Very recently, Chen et al 222 reported a porphyrin-based nMOF for SMC analyses. domethyl) cyclohexanecarboxylate as a coupling agent to connect Abs to the metal-loaded nMOFs.…”
Section: Metal-organic Framework Nanoparticles (Nmofs)mentioning
confidence: 99%
“…By utilizing this merit, mass tagging strategies were proposed to convert the detection of the desired targets into the MS readout of their encoded mass tags (MTs), which commonly feature high ionization efficiency . In addition to the most classic rare-earth elemental tags for inductively coupled plasma mass spectrometry (ICP MS) interrogation, , evolutionary MTs ranging from organic molecules, oligonucleotides, and peptides compatible with matrix-assisted laser desorption ionization mass spectrometry (MALDI MS) or electrospray ionization mass spectrometry (ESI MS) have recently been presented for the multiplexed assay of serum biomarkers, intracellular proteases and RNAs, and cell surface receptors. To further improve the detection sensitivity of mass tagging strategy, our group recently presented a mass nanotag-enabled interfacial assembly system (MNT-AS) with parallel amplification motors for MS detection of multiple RNAs in different breast cancer cell lines and their exosomes . However, the mass-encoded nanoprobes that can reflect and amplify the information on multiple biomolecules across different cellular positions in parallel remain rarely reported.…”
Section: Introductionmentioning
confidence: 99%